First results from protective ECRH diagnostics for Wendelstein 7-X. (14th June 2017) - Marsen, S.; Corre, Y.; Laqua, H.P.; Moncada, V.; Moseev, D.; Niemann, H.; Preynas, M.; Stange, T.
Abstract: Wendelstein 7-X (W7-X) is a steady state capable optimised stellarator. The main heating system is electron cyclotron resonance heating (ECRH) operating at 140 GHz providing up to 9 MW microwave power. The power is launched into the machine by front steerable quasi-optical launchers in X- or O-mode. While in X-mode the first pass absorption is 99%, it is only 40... 70% in O-mode. O2-mode heating is forseen for high density operation above the X2 cutoff density of 1.2 ⋅ 10 20 m −3 . A set of diagnostics has been developed to protect the machine from non absorbed ECRH power which can easily damage in vessel components. The non absorbed power hitting the inner wall is measured by waveguides embedded in the first wall (ECA diagnostic). In order to prevent the inner wall from overheating or arcing, a near-infra red sensitive video diagnostic with a dynamic range of 450...1200 °C was integrated in the ECRH launchers. Thermal calculations for the carbon tiles predict a temperature increase above the detection threshold for scenarios of plasma start-up failure or poor absorption on a time scale of 50 ms. However, the temperature increase measured by an IR camera in experiments with failed break down, i.e. no ECRH absorption for up to 50 ms, was only Δ T ≈ 70   ∘ C. In discharges with ≈ 5% transmission the measured temperature increase was comparable. The stray radiation level inside the machine is measured by so called sniffer probes resembling microwave diode detectors which were designed to collect all radiation approaching the probing surface independent of incident angle and polarization. Five sniffer probes are installed at different toroidal positions. They were integrated in the ECRH interlock system. During the first operational phase of W7-X this was the only available plasma interlock system. The signal quality proofed to be high enough for a reliable termination in case of poor absorption. After a breakdown phase of 10 ms, the sniffer probe signals dropped by more than an order of magnitude. Especially in the very first days of operation, most discharges died by a radiative collapse due to impurity influx. In this case the heating power was reliably switched off due to the increased level of stray radiation. Moreover, ECRH bolometers with a slower response time in the launcher ports and an empty diagnostic port were used to estimate the stray radiation level in the ports. In the launcher ports it could be shown that the stray radiation could lead to an overheating of the bellows in long discharges. Possible counter measures are discussed.